Enhancing Higher-Order Thinking Skills in Elementary Science Learning Using the RADEC Model - Shinta Sunny Oktadila; Hadi Nasbey; Indra Jaya (Postgraduate, University of Mataram, 2025)
This study aims to determine the effectiveness of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model in improving Higher Order Thinking Skills (HOTS) in science learning of fifth grade elementary school students in Palembang City. This study used an experimental method with a posttest-only control group design. This study involved 48 fifth grade elementary school students in Palembang City who were divided into experimental groups (n = 24) and control groups (n = 24). Data collection was carried out through a HOTS Science test on the material Magnets, Electricity, and Technology for Life. The form of questions used, namely multiple-choice questions and essay questions, has been tested for validity and reliability. The results of the analysis using the t-test showed that there was a significant effect of the RADEC model on improving students' HOTS (sig. 0.028 <0.05). The average HOTS post-test score of the experimental class was higher than the control class (76.96 > 68.25). The findings of the study indicate that RADEC can be implemented as an alternative learning strategy to improve HOTS in elementary science learning.